MEMBANGUN KONEKSI PELANGGAN MELALUI INSTAGRAM COFFEE SHOP UNTUK MENINGKATKAN KUNJUNGAN PELANGGAN - Sitorus, David Humala; Wage, Sunarto; Rustam, Triana Ananda; Khoiri, M (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This research examines how coffee shops can leverage Instagram for digital marketing communication. Instagram is a powerful and affordable tool for cafes to promote their products, spread brand awareness, and connect with customers. Studies have shown that using Instagram strategically can inform customers about a coffee shop's offerings, persuade them to visit, and keep them coming back. However, there's a lack of research on how cafes can specifically use Instagram's features to manage their digital marketing communication with customers. This study aims to fill this gap by exploring how coffee shops can effectively use Instagram as a marketing tool. The researchers used interviews and data analysis to gain insights from coffee shop visitors with a research time-period of 3 months. The study confirms that Instagram is a cost-effective way for cafes to quickly reach customers with their promotional messages, compared to traditional marketing methods. The sample in this study amounted to 100 respondents. Technique sampling method using the Slovin formula. This type of research is quantitative research which has the aim of finding relationships between variables in a population. The nature the research is in the form of replication. The resulting data was analyzed using validity and reliability tests, for classical assumption tests using normality tests, heteroscedasticity tests, and multicollinearity tests. hypothesis testing in this study is multiple linear regression analysis test, coefficient of determination test, t test and f test with the help of SPSS 25.